2006
DOI: 10.1593/neo.06283
|View full text |Cite
|
Sign up to set email alerts
|

Three-Color FISH Analysis of TMPRSS2/ERG Fusions in Prostate Cancer Indicates That Genomic Microdeletion of Chromosome 21 Is Associated with Rearrangement

Abstract: The recent description of novel recurrent gene fusions in approximately 80% of prostate cancer (PCa) cases has generated increased interest in the search for new translocations in other epithelial cancers and emphasizes the importance of understanding the origins and biologic implications of these genomic rearrangements. Analysis of 15 PCa cases by reverse transcription-polymerase chain reaction was used to detect six ERG-related gene fusion transcripts with TMPRSS2. No TMPRSS2/ETV1 chimeric fusion was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
131
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 21 publications
14
131
2
4
Order By: Relevance
“…First demonstrated by Yoshimoto et al 15 with three-color FISH, Perner and co-workers showed deletion in B70% of cases, similar to our observation (21/27, 81%). This finding raises the possibility that the TMPRSS2-ERG fusion event, in addition to ERG activation, is often accompanied by variable losses of intervening genes.…”
Section: Tmpress2-erg In Prostate Cancer Jj Tu Et Alsupporting
confidence: 92%
See 3 more Smart Citations
“…First demonstrated by Yoshimoto et al 15 with three-color FISH, Perner and co-workers showed deletion in B70% of cases, similar to our observation (21/27, 81%). This finding raises the possibility that the TMPRSS2-ERG fusion event, in addition to ERG activation, is often accompanied by variable losses of intervening genes.…”
Section: Tmpress2-erg In Prostate Cancer Jj Tu Et Alsupporting
confidence: 92%
“…All but one case were negative for TMPRSS2-ETV1 fusion, and similar ETV1 downstream mRNA levels were seen in all but three fusion-negative cases. 14 Soller et al 13 Yoshimoto et al 15 Tomlins et al 6 Current study (#) Table 3. Tumors with TMPRSS2-ERG fusions more frequently had focal intraluminal mucin, amphophilic cytoplasm and cribriform architecture.…”
Section: Tmpress2-erg In Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The higher-MW PCR product from sample PT335 corresponds to fusion of TMPRSS2 (exon1) to ERG (exon3), and a lower-MW PCR product from sample PT316 (not shown) corresponds to fusion of TMPRSS2 (exon2) to ERG (exon5); both variants have been previously reported. 15,17 Variant TMPRSS2-ERG in prostate cancer J Lapointe et al…”
Section: Resultsmentioning
confidence: 99%